2017
DOI: 10.1111/1747-0080.12343
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of malnutrition inflammation score, anthropometry and biochemical parameters in assessing the difference in protein‐energy wasting between normal weight and obese patients undergoing haemodialysis

Abstract: MIS was significantly better in obese patients; however, both groups showed degrees of wasting based on MIS and other PEW parameters. Nutritional status of obese haemodialysis patients should be monitored regularly because of high risk of PEW like other BMI categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
3
5
1
3
Order By: Relevance
“…The results of this study showed lower levels of cholesterol and LDL in HD/non‐DM and HD/DM patients compared to DM group. We have previously reported that a considerable percentage of patients with hemodialysis had cholesterol, LDL and TG levels below the cutoff values of hyperlipidemia . The decrease in lipids has been also reported in other studies, despite the high prevalence of cardiovascular disorders in uremia, which might be related to inflammation and poor nutritional status …”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The results of this study showed lower levels of cholesterol and LDL in HD/non‐DM and HD/DM patients compared to DM group. We have previously reported that a considerable percentage of patients with hemodialysis had cholesterol, LDL and TG levels below the cutoff values of hyperlipidemia . The decrease in lipids has been also reported in other studies, despite the high prevalence of cardiovascular disorders in uremia, which might be related to inflammation and poor nutritional status …”
Section: Discussionsupporting
confidence: 70%
“…We have previously reported that a considerable percentage of patients with hemodialysis had cholesterol, LDL and TG levels below the cutoff values of hyperlipidemia. 21 The decrease in lipids has been also reported in other studies, 22 despite the high prevalence of cardiovascular disorders in uremia, which might be related to inflammation and poor nutritional status. 21,22 Serum adipolin had a negative correlation with TG and TG/HDL ratio in patients with diabetes 12 and a positive association with HDL in CAD.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Rispetto agli studi degli anni ottanta e novanta 4,5 , la CDDP prevede una dieta ipoproteica meno severa (0,6 g/kg/die), sempre ipofosforica e normocalorica, con dieta libera in proteine il giorno della dialisi per coprire l'aumentato fabbisogno azotato legato alle perdite di proteine e aminoacidi dovute alla seduta di emodialisi. 14 I pazienti reclutabili devono essere in stato metabolico stazionario e conservare una funzione renale residua tra 5 e 12 mL/min/1,73 mq. Condizione indispensabile è la motivazione e la buona aderenza alla terapia nutrizionale prescritta.…”
Section: Cenni Metodologici Introduttiviunclassified
“…Rispetto agli studi degli anni ottanta e novanta 4,5 , la CDDP prevede una dieta ipoproteica meno severa (0,6 g/kg/die), sempre ipofosforica e normocalorica, con dieta libera in proteine il giorno della dialisi per coprire l’aumentato fabbisogno azotato legato alle perdite di proteine e aminoacidi dovute alla seduta di emodialisi. 14…”
Section: Cenni Metodologici Introduttiviunclassified